Asian public concern over the ethics of scientists: predictors and implications for research ethics - Kamarulzaman, A.; Smolak, A.; Gorroochurn, P.; Janjua, N. (Taylor & Francis, 2012)
The following two research questions were examined in this study:1)What is the public’s level of concern with ethics in science; and 2)Are religious affiliation, religious involvement, and education predictors of that concern in Asia? The sample includes 7,963 men and women between the ages of 20 and 59 from ten Asian countries. An overall low level of relative concern toward ethics in science was reported. Lower educational attainment was associated with lower odds of concern. Christian religious affiliation and moderate religious involvement were also associated with lower odds of concern.This article highlights the importance of more active research into social perspectives on ethics in science.